Secretome profile of Cellulomonas sp. B6 growing on lignocellulosic substrates - Piccinni, Florencia Elizabeth; Ontañon, Ornella Mailén; Ghio, Silvina; Sauka, Diego Hernan; Talia, Paola Mónica; Rivarola, Maximo Lisandro; Valacco, María Pía; Campos, Eleonora (Wiley; Society for Applied Microbiology, 2019)
Aims: Lignocellulosic biomass deconstruction is a bottleneck for obtaining biofuels and value‐added products. Our main goal was to characterize the secretome of a novel isolate, Cellulomonas sp. B6, when grown on residual biomass for the formulation of cost‐efficient enzymatic cocktails. Methods and Results: We identified 205 potential CAZymes in the genome of Cellulomonas sp. B6, 91 of which were glycoside hydrolases (GH). By secretome analysis of supernatants from cultures in either extruded wheat straw (EWS), grinded sugar cane straw (SCR) or carboxymethylcellulose (CMC), we identified which proteins played a role in lignocellulose deconstruction. Growth on CMC resulted in the secretion of two exoglucanases (GH6 and GH48) and two GH10 xylanases, while growth on SCR or EWS resulted in the identification of a diversity of CAZymes. From the 32 GHs predicted to be secreted, 22 were identified in supernatants from EWS and/or SCR cultures, including endo‐ and exoglucanases, xylanases, a xyloglucanase, an arabinofuranosidase/β‐xylosidase, a β‐glucosidase and an AA10. Surprisingly, among the xylanases, seven were GH10. Conclusions: Growth of Cellulomonas sp. B6 on lignocellulosic biomass induced the secretion of a diverse repertoire of CAZymes. Significance and Impact of the Study: Cellulomonas sp. B6 could serve as a source of lignocellulose‐degrading enzymes applicable to bioprocessing and biotechnological industries.